PENGEMBANGAN AGROWISATA KEBUN JERUK AMPERA WONOSARI DI KABUPATEN BOALEMO PROVINSI GORONTALO. - Desrika Talib (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2021)
Ampera Wonosari Orange Garden is the only agri tourism in Boalemo Regency. The Ampera Wonosari orange orchard is managed independently by Mr. Jadi Purwanto which is located in Panggea Village, Ampera Hamlet, Wonosari District. Ampera Wonosari Citrus Gardens Agri tourism is still classified as undeveloped agri tourism, this is influenced by its not yet optimal in terms of management, and the need for facilities and infrastructure to support tourism activities. The location of the Ampera Wonosari Orange Garden Agri tourism is far from the main road so it is difficult for tourists to go to tourist attractions and there are no signposts. Ampera Wonosari Citrus Garden Agri tourism has also not carried out promotional activities so that not many tourists know information about Ampera Wonosari Orange Garden Agri tourism. This research method uses SWOT analysis. The results of this study are to present a development strategy which in its development can cooperate with the village government and local communities and can carry out promotional activities through social media and can add facilities and infrastructure that do not yet exist in Ampera Wonosari Orange Garden Agri tourism.